The utilization of e-subpoena system in the different police stations and forensic units in Baguio City and Benguet Province: Basis for system’s improvement - Arceo, Felix Joshua (Technium Social Sciences Journal, 2025)
The effective integration of technology in law enforcement processes is crucial for enhancing efficiency, particularly in ensuring timely court appearances by police personnel. It examines the system's impact on attendance and punctuality in court proceedings, highlighting barriers to its optimal use. This study investigates the utilization of the E-Subpoena System across various police stations and forensic units in Baguio City and Benguet Province to identify challenges and propose improvements. The key informants of this study were composed of two (2) Forensic Chemists from Baguio City Forensic Unit and Regional Forensic Unit CAR, as well as the fifteen (15) police officers in different police stations in Baguio City and the province of Benguet who have experience with the E-Subpoena System. The study is academically significant as it contributes to the growing body of literature on technology adoption in law enforcement while addressing a practical gap in ensuring seamless coordination between courts and police units. A mixed-methods approach was employed, utilizing surveys and open-ended questions to gather qualitative and quantitative data from police officers who use the system. Findings reveal technical issues such as system glitches, poor internet connectivity, and delayed subpoena uploads by courts, which occasionally disrupt court attendance and preparedness. Despite these challenges, the system generally facilitates efficient monitoring of subpoenas, with personnel demonstrating commendable compliance. However, limited access points, insufficient coordination between courts and law enforcement, and a lack of system updates exacerbate existing inefficiencies. The study concludes that while the E-Subpoena System is a valuable tool, its potential is undermined by technical and procedural gaps. Addressing these gaps through improved infrastructure, enhanced coordination, and policy refinements can significantly boost system reliability and user satisfaction. Practical implications include recommendations for technical upgrades, the development of a mobile-friendly application, and increased training for system operators. These measures will not only ensure timely court appearances but also reinforce accountability and strengthen judicial processes, thereby setting a benchmark for other regions aiming to enhance their E-Subpoena system.